Next-generation adjuvant systems containing furfurman drives potent adaptive immunity and host defense as a foot-and-mouth disease vaccine adjuvant - Kim, Hyeong Won; Shin, Seokwon; Park, So Hui; Park, Jong-Hyeon; Kim, Su-Mi; Lee, Yoon-Hee; Lee, Min Ja (Frontiers in Immunology, 2024)
IntroductionMany countries use commercial foot-and-mouth disease (FMD) vaccines to prevent FMD pandemics, but these vaccines have disadvantages, such as repeated vaccinations due to the short persistence of antibody (Ab) titers and incomplete host defense despite high Ab titers. To address these shortcomings, we aimed to develop a novel FMD vaccine containing furfurman as an adjuvant.MethodTo demonstrate the efficacy of the test vaccine, adaptive immunity was evaluated by measuring Ab and neutralizing Ab titers and host defense against viral infections in experimental and target animals. In addition, the expression levels of cytokines [interferon (IFN)α, IFNβ, IFNγ, interleukin (IL)-1β, IL-2, and IL-12p40] were evaluated at the early stages of vaccination to confirm the simultaneous induction of cellular and humoral immune responses induced by the test vaccine.ResultThe groups that received vaccine containing furfurman showed a strong early, mid-term, and long-term immune response and host defense against viral infections compared to the control groups. The significant upregulation observed in cytokine levels in the furfurman group compared to those in the control groups strongly suggest that the test vaccine strengthens cellular immune response and effectively induces a humoral immune response.ConclusionOur study demonstrated that furfurman, as an FMD vaccine adjuvant, achieves long-lasting immunity and host defense against viral infections by eliciting potent cellular and humoral immune responses. Therefore, our findings contribute to the design of next-generation FMD vaccines and highlight the potential application of furfurman as an adjuvant for other viral diseases.